2020
DOI: 10.1111/jgs.16836
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Delirium Biomarkers and Their Alignment with the NIA‐AA Research Framework

Abstract: To identify whether delirium biomarkers aligned with the National Institute on Aging-Alzheimerʼs Association (NIA-AA) research framework, a conceptual model that describes the use of diagnostic biomarkers for Alzheimerʼs disease and other related dementias (ADRD). DESIGN: Systematic review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. SETTING: Acute care and outpatient settings. PARTICIPANTS: Adults diagnosed with delirium. METHODS AND MEASUREMENTS: MEDLINE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…Methods and results of study quality assessment have been previously published. 7 Of the 113 studies that met the criteria for initial systematic review, 38 studies examined the relationship between ICU delirium and fluid biomarkers. All studies focused on serum biomarkers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods and results of study quality assessment have been previously published. 7 Of the 113 studies that met the criteria for initial systematic review, 38 studies examined the relationship between ICU delirium and fluid biomarkers. All studies focused on serum biomarkers.…”
Section: Resultsmentioning
confidence: 99%
“…The search strategy and full inclusion/exclusion criteria were previously described in detail. 7 Briefly, Ovid MEDLINE, PsycInfo, Embase, and the Cochrane Library were searched for articles published between January 1, 2000, and February 20, 2020, using a combination of controlled vocabulary, keywords, and Medical Subject Headings terms pertaining to the concepts of delirium and biomarkers in the AT(N)-X framework. 6 Inclusion criteria for the search were as follows: (1) patients' age 18 years or older, (2) use of standardized delirium screening tools or diagnostic assessments, and (3) biomarker measurements listed in AT(N)-X categories (regardless of the modality used).…”
Section: Search Criteria and Strategymentioning
confidence: 99%
“…A previous systematic review identified 113 delirium biomarker studies that aligned with the National Institute on Aging -Alzheimer's Association (NIA-AA) research framework 63 , which defines AD using biomarkers that reflect underlying pathological processes 64 . Many of these studies focused on inflammatory cytokines and about 20% of studies explored known AD biomarkers such as amyloid, tau and/or markers of neurodegeneration.…”
Section: Diagnosismentioning
confidence: 99%
“…Furthermore, some patients with AD biomarkers did not develop delirium after surgical treatment of hip fracture 91,92 , suggesting that the presence of AD pathology does not guarantee the development of delirium in response to this precipitant. Review of the existing literature on delirium biomarkers found that many studies either did not include known AD biomarkers, the quality of biomarker data was moderate or had a high risk of bias, or the cognitive data was limited 63 .…”
Section: Nature Reviews | Neurologymentioning
confidence: 99%
“…In this issue of International Psychogeriatrics, Wang and colleagues present a systematic review and meta-analysis on the relationship between POD and disease-state biomarkers of Alzheimer's disease and related dementias (ADRD) (Wang et al, 2022). This publication builds upon their prior review (Wang et al, 2020) by focusing on the subset of studies specific to POD and evaluating the relationship of each biomarker with POD through meta-analysis. The authors use the National Institute on Aging -Alzheimer's Association (NIA-AA) AT(N) Diagnostic Framework for Alzheimer's disease (AD), which categorizes biomarkers as amyloid (A), tau (T), and neurodegeneration (N) while allowing additional biomarkers such as vascular or synuclein to be designated by an X (Jack et al, 2018).…”
mentioning
confidence: 99%